Dakwah di Tengah Pluralitas Masyarakat - Samsudin Samsudin (Communicative : Jurnal Dakwah dan Komunikasi, 2021)
Da'wah is an activity carried out to provide enlightenment to the community. Da'wah is designed in a variety of common ways so that people accept the teachings of Islam. Substantively da'wah invites and invites people to accept the truth. Da'wah is not an activity that contains coercion and violence. The reality of da'wah shows that da'wah is always in the midst of the cultural plurality of society. In this context, da'wah sometimes tends to be forced without considering the plurality of backgrounds. One of the factors causing tension in the community is because da'wah is not formulated wisely and often negates the facts of plurality. Therefore, da'wah is actually formulated in a friendly manner, other than because it is in accordance with the recommendations of Islamic teachings, the transfer of Islamic teachings will be very easy to do. Plurality as sunnatullah is a legacy that must be appreciated and ammunition that can be used to strengthen the process of carrying out da'wah. There is a lot of da'wah wisdom that can be explored in society from this plurality. Related to this, religious speakers who appear must be equipped with various approaches and materials for da'wah based on plurality values. Religious speakers must be responsive in responding as well as having intelligent thoughts to manage this plurality. The da'wah material delivered must be soothing and embracing all parties, not material that is harsh and tends to make society polarized and tense. The old da'wah paradigm that is oriented towards increasing the number of followers must be changed by improving the quality and standard of living of the community. Da'wah material should be more related to common challenges than material that only teaches personal piety and ignores universal humanitarian issues.